Pax2/5/8 and Pax6 alternative splicing events in basal chordates and vertebrates: a focus on paired box domain - Fabian, Peter; Kozmikova, Iryna; Kozmik, Zbynek; Pantzartzi, Chrysoula N. (Frontiers in Genetics, 2015)
Paired box transcription factors play important role in development and tissue morphogenesis. The number of Pax homologs varies among species studied so far, due to genome and gene duplications that have affected PAX family to a great extent. Based on sequence similarity and functional domains, four Pax classes have been identified in chordates, namely Pax1/9, Pax2/5/8, Pax3/7 and Pax4/6. Numerous splicing events have been reported mainly for Pax2/5/8 and Pax6 genes. Of significant interest are those events that lead to Pax proteins with presumed novel properties, such as altered DNA-binding or transcriptional activity. In the current study, a thorough analysis of Pax2/5/8 splicing events from cephalochordate and vertebrates was performed. We focused more on Pax2/5/8 and Pax6 splicing events in which the paired domain is involved. Three new splicing events were identified in Oryzias latipes, one of which seems to be conserved in Acanthomorphata. Using representatives from deuterostome and protostome phyla, a comparative analysis of the Pax6 exon-intron structure of the paired domain was performed, during an attempt to estimate the time of appearance of the Pax6(5a) mRNA isoform. As shown in our analysis, this splicing event is absent in basal chordates and is characteristic of Gnathostomata. Moreover, expression pattern of alternative spliced variants was compared between basal chordates and fish species. In summary, our data indicate expansion of alternative mRNA variants in paired box region of Pax2/5/8 and Pax6 genes during the course of vertebrate evolution.